CAF08 adjuvant enables single dose protection against respiratory syncytial virus infection in murine newborns - Simon D. van Haren; Gabriel K. Pedersen; Azad Kumar; Tracy J. Ruckwardt; Syed Moin; Ian N. Moore; Mahnaz Minai; Mark Liu; Jensen Pak; Francesco Borriello; Simon Doss-Gollin; Elisabeth M. S. Beijnen; et al. (Nature Communications, 2022)
Respiratory syncytial virus is a major pathogen with burden observed and associated with childhood infection. Here the authors characterise a cationic adjuvant formulation and show single immunisation results in protection in a murine neonate model of respiratory syncytial virus infection.